Acute Leukemias - Paolo Piccaluga, Pier (IntechOpen, 2021)
Written by expert research teams, this book describes different aspects of both acute myeloid and acute lymphocytic leukemia, specifically their pathobiology, classification/diagnosis, and treatment. Chapters highlight current research as well as the gold standards for diagnosis and treatment of these diseases, examining recent advances in personalized approaches to acute leukemia.